A physician’s odyssey to an MBA - Stellato, Thomas A. (Butterworth-Heinemann, 2002)
Dr. Stellato explains why, at middle age, he decided to interrupt his successful practice, disrupt his family, and spend a great deal of money to obtain his MBA. Honest and compelling, the unique diary format presents Dr. Stellato's experiences as they occurred at the prestigious Weatherhead School of Management at Case Western Reserve University followed by helpful after-the-fact introspective reflections